Optimization of movement skills assessment in physical education learning using online self and peer assessment - Gema Fitriady; Mohammad Alfarizi Mohammad Alfarizi; Surya Adi Saputra (CV Rezki Media, 2022)
The obstacle for physical education (PE) teachers during COVID-19 was conducting video assessments of students' movement skills one by one so that the teacher's focus was dominant on assessing. This study aims to examine the effectiveness of self-and peer assessment of the skills of Pencak silat front kicks in Physical Education subjects. The method used is a comparative causal method with a quantitative approach. The selection of the sample is by using the incidental sample technique in class VIII students of SMP Negeri 3 Malang. The data obtained was in the form of self-, peer, and teacher assessments on the material for Pencak silat front kicks using an online application. The results of the different tests using the Wilcoxon Signed Test obtained a P value > 0.05 so that the data did not differ between the comparison of self- (SA) and peer assessments (PA) and the teacher's assessment (TA). Self-assessment and peer assessment was declared effective in assessing movement skills, especially the material for the Pencak silat front kick.